GEOGRAPHIC INFORMATION SYSTEM (GIS) WEB SERVER FOR BIODIVERSITY INFORMATION SYSTEM - DJAMALUDDIN, IBRAHIM; INDRAYANI, POPPY; MITANI, YASUHIRO; TAGANE, SHUICHIRO; YAHARA, TETSUKAZU (REINWARDTIA, 2015)
DJAMALUDDIN, I., INDRAYANI, P., MITANI, Y., TAGANE, S. & YAHARA, T. 2015. Geographic Information System (GIS) web server for biodiversity information system. Reinwardtia 14 (2): 249 - 258. - Ecological protection strategies, designed by sharing information and integrating data, play an important role in defining interconnections and interdependencies in research as well as in increasing global awareness. The Geographic Information System (GIS) web server is one technology solution to improve the interoperability and sharing between the biodiversity databases of an organization and the databases of other research groups. In this paper, a database system integration framework based on GIS technology and a GIS server system using the latest cloud-based technology have been developed to incorporate biodiversity databases in Asian region. A GIS server is a GIS web platform integrating multiple geodatabases and provides data display and query, allowing users to apply internet browsers to manipulate the functions and query the data, etc. To demonstrate the effectiveness of a GIS web server, plant biodiversity survey dataset of Mt. Gede Pangrango, West Java in Indonesia, was given as a case study for development and utilization of biodiversity information system in Asian region.